CONSIDERATIONS FOR BRITTLENESS IN TAILINGS - Jiří Herza; Ryan Singh (Acta Polytechnica CTU Proceedings)
Brittleness is an important geotechnical parameter of soils as it describes the degree of reduction of the soil shear resistance after reaching the peak strength. [1] described soil brittleness by means of a brittleness index (IB), which is the ratio of the shear resistance loss to the peak shear strength. The IB has become a common soil parameter that is used as an indicator for the soil susceptibility to liquefaction. However, IB does not consider the rate at which the soil resistance reduces, the development of excess pore water pressure and it ignores the stress strain relationship. As a result the same IB can be calculated for a soil that collapses over a very small strain range and a soil that gradually reduces its shear resistance over extensive strain levels as long as both soils have similar peak and residual shear strengths. This paper discusses the root causes of the shear resistance loss and proposes a modification of the IB parameter to take account of the rate of the shear resistance loss, which will help to better depict the stress-strain behaviour of strain softening soils. This paper also distinguishes between structural brittleness and undrained brittleness and provides a clear definition of each to improve the understanding of tailings among practitioners.